RELATIONSHIP OF MOTOR DEVELOPMENT OF CHILDREN AND ADOLESCENTS WITH BODY TYPE AND MORPHOFUNCTIONAL FEATURES - Ponomarev, G.N.; Komissarova, E.N.; Rodichkin, P.V.; Zelensky, K.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the relationship between the motor development of children and adolescents and the body type and their morphofunctional features. Methods and structure of the study. The experiment involved 1415 children aged 4-7, 25 schoolchildren aged 7(8) to 10 years and 45 teenagers aged 11-16 playing handball. The work used: anthropometry according to P.N. Bashkirov and somatotyping according to R.N. Dorokhov, tapping test and RMO, assessment of morphometric parameters of the muscles of the lower extremities "MORFOMETR", digital dermatoglyphics according to the method of T.F. Abramova, bioimpedance analysis and a battery of motor tests. Results and conclusions. A correlation was established between the development of the physical qualities of children of different ages and their body types. In addition, the dependence of somatotypes and morphometric parameters of the muscles of the upper and lower extremities, the speed of muscle contraction and indicators of digital dermatoglyphics, as well as hereditary predisposition, has been established.